Chapter 4 Self-Harm as Violence When Victim and Perpetrator Are One - Widdows, Heather (Genders and Sexualities in the Social Sciences, 2015)
This edited collection explores the agency of women who do violence and have violence done to them. Topics covered include rape, pornography, prostitution, suicide bombing and domestic violence. The volume contributes to the philosophical and theoretical debate, as well as offering practical, social and political responses to the issues examined.